English raising predicates and (non-)finite clauses : diachronic and synchronic perspectives - Lenardič, Jakob (Array, 2019)
In this paper, we present a diachronic and synchronic analysis of raising and extraposition constructions in the historical Brown Corpus and the more contemporary English Web Corpus 2015. We begin by establishing two diachronic facts: first, raising constructions are used much more frequently than their semantically equivalent extraposition variants, and second, the distribution of raising and extraposition remains – rather exceptionally in comparison to other structures allowing for finite/non-finite variation – diachronically consistent from the beginning of the 20th century to 2015. We then supplement this unique diachronic distribution with an analysis of the most recent corpus data, which shows that the choice between the two semantically equivalent constructions is governed by distinct structural factors unique to each construction. Concretely, we show that the raising construction is frequently used as a relative clause, whereas the extraposition variant generally resists such a syntactic role. By contrast, we show that a prominent factor in favour of extraposition relates to the negative marker, which is placed with similar frequency both in the matrix and in the embedded clause of the extraposition construction in contrast to the raising variant, which uses the negative marker almost exclusively in the matrix clause. Lastly, we show that extraposition constructions contain modal verbs in the matrix clause more frequently than the raising variants and we tie this observation to the idea that the clausal composition of the extraposition construction is structurally more suited for expressing tentativeness.